The Judeo-Spanish Literature - Diaz- Mas, Paloma; Alexander, Tamar (MiKAN, 2007)
This contribution is a a comprehensive survey ofthe literature produced in Ladino by Sephardic Jews from the 16th to the 20th centuries, with special attention to the period between 18th and the first decades of 20th centuries, both in North Africa and in the Eastern Mediterranean communities ofthe lands that once belonged to the Ottoman Empire. Sections are devoted to translations ofthe Bible to Ladino, other religious works, including Me'am Lo'ez, the main Rabbinic commentary of the Bible in Judeo-Spanish, the genre of learned poetry called coplas, the folk sephardic literature (proverbs, folktales, balladry), and the so-called adoptedgenres. These are the modem literature that follows occidental literary patterns, produced from the 19th century onward -journalism, novels, theatre, and modem poetry. At the end of each section, useful bibliographical references are provided.